Malecón Ecoturístico Comercial (2023)
The main theme of the degree work was focused on an Ecoturism – Commercial Malecon for the municipality of Melgar in the department of Tolima, as a solution to the problem of spatial and evironmental disarticulation, a proliferation of illegal settlements on the Sumapaz River and the segregation of uses on the urban perimeter. It was decided to work in Melgar and not in another municipality, seeking to demostrate how, from urban design, it is important to carry out interventions that seel to articulate all these sectors that are in that condition of segregation, followed by the configuration of an urban fabric that provides conditions for both spatial and environmental quality